Analisis Levelized Cost of Energy Pelet Kayu (Levelized Cost of Energy Analysis of Wood Pellet) - Bintang CH Simangunsong; Ganesha SJ Silalahi; Mohammad DG Maulana; Elisa GT Manurung; Vera J Sitanggang; Armansyah H Tambunan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
The availability of fossil energy resources as an input of production is limited and eventually will be rare. One of potential alternative energy that is recently developed to partly substitute fossil fuels based energy is wood pellet. The objective of this research was to analyze the levelized cost of energy (LCoE) of wood pellet made from wood processing residues. LCoE was the minimum energy prices that should be sold for an energy project to break even. The LCoE of wood pelet was obtained about IDR 259 per kWh or USD 0.02 per kWh. This LCoE value is lower than the LCoE of fossil fuels. It is indicating that energy derived from wood pellet is a very competitive.Keywords: LCoE, renewable energy, wood pellet, wood industry, wood residues